Myeloid-Derived Suppressor Cells in Pregnancy and the Neonatal Period - Köstlin-Gille, Natascha; Gille, Christian (Frontiers in Immunology, 2020)
During pregnancy the immune systems of mother and offspring are challenged by their close adjacency to balance tolerance and rejection. After birth the neonate has to continue this balance towards its new environment by tolerating commensals while rejecting pathogens and towards its developing tissues to avoid inflammatory damage while overcoming immunosuppression. Our group was the first to link immunosuppressive features of myeloid derived suppressor cells (MDSC) to materno-fetal tolerance, neonatal susceptibility to infection and inflammation control. Here we summarize recent advances in this dynamic field.